2009
DOI: 10.1002/jmv.21538
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of dengue infected human primary cells identifies secreted mediators in vivo

Abstract: We used gene expression profiling of human primary cells infected in vitro with dengue virus (DENV) as a tool to identify secreted mediators induced in response to the acute infection. Affymetrix Genechip analysis of human primary monocytes, B cells and dendritic cells infected with DENV in vitro revealed a strong induction of monocyte chemotactic protein 2 (MCP-2/CCL8), interferon gamma-induced protein 10 (IP-10/CXCL10) and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL/TNFSF10). The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 36 publications
1
38
1
2
Order By: Relevance
“…However, CXCL10 function specific to DENV infection has not been examined in vivo. Recent studies have shown that CXCL10 is the most highly upregulated gene in dengue patient blood samples (26), in muscle satellite cells exposed to DENV in vitro (27), and in primary human dendritic cells infected by DENV (28), supporting the suggestion that CXCL10 is critical for defense against DENV infection. In this study, we investigated the antiviral activity of CXCL10 in DENV infection.…”
Section: Engue Virus (Denv)mentioning
confidence: 80%
See 2 more Smart Citations
“…However, CXCL10 function specific to DENV infection has not been examined in vivo. Recent studies have shown that CXCL10 is the most highly upregulated gene in dengue patient blood samples (26), in muscle satellite cells exposed to DENV in vitro (27), and in primary human dendritic cells infected by DENV (28), supporting the suggestion that CXCL10 is critical for defense against DENV infection. In this study, we investigated the antiviral activity of CXCL10 in DENV infection.…”
Section: Engue Virus (Denv)mentioning
confidence: 80%
“…Our data suggest that CXCL10 participates in antiviral response independent of CXCL10-mediated leukocyte recruitment following DENV infection. Because CXCL10 is the predominant CXCR3 ligand induced by DENV infection (17,26,28) but was not critical for recruitment of effector cells, we examined other potential antiviral mechanisms. Previously, we demonstrated that CXCL10 inhibits DENV entry into hepatocytes by competing with DENV for binding to the cell surface heparan sulfate (31), a coreceptor for DENV entry (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in recent years have evaluated the host response to dengue virus infections by the use of high-throughput technologies such as microarrays (3,14,33,45). These studies generally demonstrated substantial activation of the innate immune response, mainly mediated through the presence of type I IFN.…”
Section: Vol 85 2011 Denv-3 Induces Inflammatory Responses In Mddcsmentioning
confidence: 99%
“…Cabe la hipótesis de que el incremento de la respuesta de citocinas en niños con dengue se origine a partir de células del sistema inmunitario innato (dianas para la replicación inicial de dengue) y no de las células T; por ejemplo, los experimentos in vitro muestran que los monocitos y las células dendríticas pueden actuar como una fuente importante de citocinas durante la infección por dengue (30,31). Chen, et al, (32) propusieron un modelo de patogénesis de dengue en el cual la producción de citocinas por monocitos durante la fase temprana de la infección desencadena una cascada de sucesos que eventualmente conducen a un incremento de la respuesta de citocinas y aumentan la permeabilidad vascular.…”
Section: Discussionunclassified